Clonal structure, growth pattern and preemptive space occupancy through sprouting of an invasive tree, Triadica sebifera. Issue 1 (2nd January 2017) - Moriya, Yuuki D.; Nanami, Satoshi; Sumikura, Jun-ichi; Yamakura, Takuo; Itoh, Akira
ABSTRACT: We investigated clonal structure, growth pattern and colonization through sprouting in the invasive tree species Triadica sebifera on Mt. Mikasa, Nara City, Japan. Genets of T. sebifera were identified by microsatellite DNA analysis. The age of stems was determined by counting annual growth rings. In a 25 × 60-m plot, we found 214 genets among 315 stems ≥130 cm in height. Of these, 23 genets were multistemmed. Numbers of stems on a genet increased with increasing genet age. The size, shape and number of stems indicated that several genets adopted a guerilla growth strategy in which stems are widely spaced along roots. Only one genet seemed to adopt a phalanx growth strategy characterized by high stem density within limited areas. Older stems occurred only in the vicinity of the parental stems of genets. Young stems occurred not only at the leading edge of the genet but also close to the parental stem. Stem size was negatively correlated with the number of younger stems but positively correlated with that of older stems on the same genet. This suggests that stems were physiologically connected and that translocation of photosynthetic products was directed from old to young stems. Physiological integration may allow small stems to persist under low light availability. These findings indicate that urgent measures are required to control the T. sebifera population because the species increases its area of occupancy by vigorous stem sprouting which may compromise the natural forest.